Regulating Shipping in the Arctic Ocean: An Analysis of State Practice. (3rd July 2018) - Hartmann, Jacques
Abstract : The United Nations Convention on the Law of the Sea (LOSC) permits state parties to establish an Exclusive Economic Zone (EEZ) 200 nautical miles from their coast. Coastal states have exclusive jurisdiction over resources within the EEZ, but navigational and other high seas freedoms continue to exist. A significant number of states have, however, enacted legislation that departs from the LOSC, interfering with the navigational rights and freedoms of other states. This article analzses this development with a specific focus on the Arctic. It investigates the powers of Arctic coastal states to regulate shipping in the EEZ and thereby navigation in the Arctic Ocean. It adds to the existing literature by providing an analysis of state practice, suggesting that despite uncertainty concerning the interpretation of the LOSC Article 234 and the right to exercise legislative jurisdiction over ice-covered waters, a not insignificant number of states have claimed jurisdiction in their own EEZ beyond the rights granted in the LOSC, and are therefore not in a position to object to extensive jurisdictional claims in the Arctic.